Oxynemamangrovii sp. nov., a new filamentous species (Oscillatoriales, Cyanobacteria) from Atlantic forest mangrove - Apaza-Castillo, Gladys A.; Dextro, Rafael B.; Andreote, Ana P. D.; Souza, Bruno C. E.; Hosaka, Guilherme K.; Delbaje, Endrews; Branco, Luis H. Z.; Riaño-Pachón, Diego M.; Fiore, Marli F. (Frontiers in Microbiology, 2026)
A cyanobacterial strain isolated from Brazilian mangrove soil and classified as a member of the genus Phormidium was afterward affiliated to the genus Oxynema. To define the species of this Oxynema strain CENA135, we sequenced its whole genome and applied a polyphasic taxonomic approach. This strain, with all the morphological features recognized for the Oxynema genus, had its genome assembled in 11 scaffolds with a total size of 6,235,022 bp, a G + C content of 51.6%, 4,720 protein-coding genes, and five 16S rRNA genes. Genes related to ecological resistance were annotated, demonstrating the relevance of obtaining high-quality genome assemblies from underrepresented habitats. A phylogenomic tree inferred by GTDB-Tk based on the alignment of 120 conserved proteins clustered Oxynema sp. CENA135 together with the strain Oxynema aestuarii AP17 isolated from Indian mangrove soil, and digital DNA–DNA hybridization and average nucleotide identity values between these two strains were 92.8 and 95.78%, respectively. Phylogenetic analysis based on 16S rRNA gene sequences placed the strain CENA135 in a separate and well-supported major clade (100% bootstrap) containing Oxynema species, and its 16S rRNA gene sequence showed identity ≤98.6% compared to the other species of the genus. Moreover, the strain CENA135 had a distinct 16S–23S ITS sequence and secondary structure polymorphisms in comparison to the other Oxynema species, supporting its recognition as a novel species. On the basis of evidence from this polyphasic study, strain CENA135 should be designated as representing a novel species of the genus Oxynema, for which the name Oxynema mangrovii sp. nov. is proposed under the provisions of the International Code of Nomenclature for algae, fungi, and plants.